Behavioral determinants for glycemic control among type 2 diabetic patients in Hosanna town; institution based unmatched case control study - Belay Bancha; Begidu Bashe; Hana Seyfu; Abraham Samuel (PLoS ONE, 2025)
Backgrounds Together with other non-communicable diseases, diabetes mellitus (DM) remains main health threats to human beings throughout the world. Despite an alarming increment of its trend in Ethiopia, majority of diabetic patients failed to attain glycemic control. Thus, this study aimed at identifying modifiable lifestyles for glycemic control among patients with type 2 diabetic mellitus. Objectives To assess behavioral determinants of glycemic control among type 2 diabetic patients attending Wachemo University Nigist Eleni Mohammed Memorial Teaching Hospital (WUNEMMTH) in Hosanna, Ethiopia. Methods Institution based unmatched case control study was conducted from May15-July 15, 2023. The questionnaire was digitalized to open data kit (ODK) for android version. Data was collected by simple random sampling technique and analyzed using SPSS version 23. Descriptive and logistic regression analysis were performed. Adjusted odds ratios and 95% confidence intervals were used to measure the effect size. Level of statistical significance was declared at a p-value of < 0.05. Results From 232 expectants, 226 (cases =  113 and controls =  113) were participated, making the response rate 97.41%. After adjusting for others, non-adherence to fruit and vegetable intake (AOR = 3.38, 95% CI = 1.73-6.60), non-adherence to physical exercise (AOR = 4.94, 95% CI = 2.38-10.27), poor diabetic self-efficacy (AOR = 5.51, 95% CI = 2.85-10.66) and high body mass index (AOR = 3.68, 95% CI = 1.73-7.82) were independent determinants for poor glycemic control among T2DM clients. Conclusion and recommendations Self-efficacy and healthy lifestyle were behavioral determinants for glycemic control among T2DM patients. Thus, interventions targeting modifiable lifestyle should be an integral part of the management along with standard pharmacotherapy.